Different inhibition of Gβγ-stimulated class I(B) phosphoinositide 3-kinase (PI3K) variants by a monoclonal antibody: Specific function of p101 as a Gβγ-dependent regulator of PI3Kγ enzymatic activity - Shymanets, Aliaksei (Biochem J, 2015)
Class I(B) phosphoinositide 3-kinases (PI3Kγ) are second-messenger-generating enzymes downstream of signalling cascades triggered by G-protein-coupled-receptors (GPCRs). PI3Kγ variants have one catalytic p110γ subunit that can form two different heterodimers by binding to one of a pair of non-catalytic subunits, p87 or p101. Growing experimental data argue for a different regulation of p87-p110γ and p101-p110γ allowing integration into distinct signalling pathways. Pharmacological tools enabling distinct modulation of the two variants are missing. The ability of an anti-p110γ monoclonal antibody (mAb(A)(p110(γ))) to block PI3Kγ enzymatic activity attracted us to characterize this tool in detail using purified proteins. In order to get insight into the antibody-p110γ-interface, hydrogen-deuterium exchange coupled to mass spectrometry measurements were performed demonstrating binding of the monoclonal antibody to the C2 domain in p110γ, which was accompanied by conformational changes in the helical domain harbouring the Gβγ-binding site. We then studied the modulation of phospholipid vesicles association of PI3Kγ by the antibody. p87-p110γ showed a significantly reduced Gβγ-mediated phospholipid recruitment as compared with p101-p110γ. Concomitantly, in the presence of mAb(A)(p110(γ)) Gβγ did not bind to p87-p110γ. These data correlated with the ability of the antibody to block Gβγ-stimulated lipid kinase activity of p87-p110γ 30 times more potently than p101-p110γ. Our data argue for differential regulatory functions of the non-catalytic subunits and a specific Gβγ-dependent regulation of p101 in PI3Kγ activation. In this scenario, we consider the antibody as a valuable tool to dissect the distinct roles of the two PI3Kγ variants downstream of GPCRs.